Identification of Mesencephalic Astrocyte-Derived Neurotrophic Factor as a Novel Neuroprotective Factor for Retinal Ganglion Cells - Gao, Feng-Juan; Wu, Ji-Hong; Li, Ting-Ting; Du, Shan-Shan; Wu, Qiang (Frontiers in Molecular Neuroscience, 2017)
Mesencephalic astrocyte-derived neurotrophic factor (MANF), a newly discovered secreted neurotrophic factor, has been proven to not only protect dopaminergic neurons and other cell types but also regulate neuroinflammation and the immune response to promote tissue repair and regeneration. However, to date, there is no information regarding the relationship between MANF and retinal ganglion cells (RGCs) in the eye. In the current study, we first determined the expression of MANF in the retina and vitreous. Then, we examined the effect of MANF on RGCs using both in vivo and in vitro models and simultaneously explored the underlying neuroprotective mechanisms of MANF. Finally, we measured the concentrations of MANF in the vitreous of patients with different retinopathies. We demonstrated that MANF was highly expressed in RGCs and that exogenous MANF could protect RGCs from hypoxia-induced cell injury and apoptosis both in vitro and in vivo by preventing endoplasmic reticulum stress-mediated apoptosis. Furthermore, MANF can be detected in the vitreous humor, and the concentration changed under pathological conditions. Our results provide important evidence that MANF may be a potential therapeutic protein for a range of retinal pathologies in either the preclinical stage or after diagnosis to promote the survival of RGCs. Vitreous MANF may be a promising protein biomarker for the indirect assessment of retinal disorders, which could provide indirect evidence of retinal pathology.